The Lost Experience: estratégias de imersão em jogos de realidade alternada - Mesquita Júnior, Dario de Souza (2012)
Among the current media forms, the alternate reality games (ARG) is in the spotlights due its capability of giving a ludic experience with strong immersive qualities. Setting its fictional world in sync with everyday reality, the ARG seeks to smear the border between fiction and non-fiction, in order to intensify the experience of the audience. This research analyzes the immersion strategies of alternate reality games based on the study of The Lost Experience (LTE), with the purpose of understanding how the immersion process on the fictional world created by ARGS occurs. Therefore, the main characteristics of alternate reality games are studied, from its main principles established in order to make accessible the fictional world connected to the everyday life of the players, trough the interface of the media. In this process, the concept of immersion is problematized, in order to understand the extension this term receives in front of some perspectives that denote its nature. Visions that lead to a common denominator that connects the notion of immersion with the pleasure of being involved in a sensorial, cognitive and emotional degree towards external stimuli, that as an answer leads an action over the experienced environment. The analysis of the immersion strategies in The Lost Experience helps in the comprehension of how it sets up its fictional world in touch with everyday life, with the goal of creating immersive zones that allows the interaction of players with the elements of its universe.